2021
DOI: 10.3389/fpsyg.2021.661769
|View full text |Cite
|
Sign up to set email alerts
|

Musical Training in the Development of Empathy and Prosocial Behaviors

Abstract: Music not only regulates mood but also promotes the development and maintenance of empathy and social understanding. Since empathy is crucial for well-being and indispensable in social life, it is necessary to develop strategies to improve empathy and prosocial behaviors. To fulfill this aim, researchers have extensively investigated the effect of intensive musical training on the development of empathy. Here, we first summarize evidence showing the powerful influence of musical training on the development of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 76 publications
0
6
1
2
Order By: Relevance
“…In addition, Zhao et al (2020) found that ordinary school education may lift Chinese college students’ cognitive empathy and personal distress tandemly. The current results, in contrast, suggest that optional music training may help youths enhance cognitive empathy and dampen personal distress (also see Wu & Lu, 2021). This observation is fascinating as people can enjoy sad music without being distressed (Garrido & Schubert, 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…In addition, Zhao et al (2020) found that ordinary school education may lift Chinese college students’ cognitive empathy and personal distress tandemly. The current results, in contrast, suggest that optional music training may help youths enhance cognitive empathy and dampen personal distress (also see Wu & Lu, 2021). This observation is fascinating as people can enjoy sad music without being distressed (Garrido & Schubert, 2011).…”
Section: Discussioncontrasting
confidence: 71%
“…Investigating empathy in children's musical interaction would also complement developmental research in rhythmic perception and production (e.g., Drake et al, 2000), highlighting the possible interplay between musical training, social skills, and the motivation to synchronize with others (Kirschner & Tomasello, 2009). A suggested approach (also proposed by Wu and Lu (2021)) would be to collect comparable data over a range of ages that correspond to key milestones in the development of empathy and synchronisation, such as: (a) age five or six, when social interactions increase by attending school; (b) age ten, when the ability to synchronize with a rhythmic sequence reaches similar levels to adults (Drake et al, 2000); and (c) adolescence, when the brain regions involved in social cognition undergo dramatic changes (Blakemore, 2008). It is hypothesized that early engagement in synchronous interactions positively affects the development of empathy (Cho, 2019; Levy & Feldman, 2019), which subsequently enhances the development of cognitive-motor skills required for attaining interpersonal synchronisation.…”
Section: The Relationship Between Empathy and Interpersonal Synchroni...mentioning
confidence: 99%
“…The experience of motor mimicry and emotional contagion is highly associated with the mirror neuron system (Iacoboni, 2009 ), through which induces a similar emotional state in the observer as in the observee. Although empathy emerges and develops early in life, it is flexible and amenable over the lifespan (Decety, 2015 ), and can be affected by both intraindividual contributors and social factors (McDonald and Messinger, 2011 ; Wu & Lu, 2021 ). Since the mirror neurons come from sensorimotor experience, and much of this experience is obtained through interaction with others (Heyes, 2010 ), it is reasonable to assume physical activities involving imitation and interaction could facilitate the development of empathy.…”
Section: Introductionmentioning
confidence: 99%